Geological assessment for tunnel excavation under river with shallow overburden using surface site investigation data and electrical resistivity tomography - Ismail, Mohd Ashraf Mohamad; Majid, Taksiah A.; Goh, Chin Ong; Lim, Siao Phin; Tan, Chee Ghuan (Elsevier, 2019)
Tunnelling is a challenging task as many geotechnical uncertainties involved during construction, especially under a river crossing with shallow overburden. This study focussed on geological assessment for the New Austrian Tunneling Method excavation that crosses under Kerau River with shallow overburden. 3D filtered tunnel models using Boolean filter for rock mass weathering grade, rock quality designation, and Lugeon value are developed. Results predict that 53.3% of the tunnel excavation under the Kerau River crossing are highly weathered rocks (Grades III and IV), and 64.51% are in the moderately to highly fractured zone (0%–75% RQD) along the roof of the tunnel granitic bedrock. The Lugeon value models show that 71.64% of the excavating rocks possess a Lugeon value of 5–50 (6–60 × 10−5 cm/s), which denotes considerably high permeability. 2D electrical resistivity tomography is used to verify the permeability results from the Lugeon test. © 2019 Elsevier Ltd